KETERLAMBATAN FAKTUR & SANKSI ADMINISTRATIF: STRATEGI AKUNTANSI MENGHADAPINYA DI ERA CORETAX - Salim, Agus; Yuda Nugraha, Yongky Rangga; Nurdina, Hana (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2025)
The implementation of the CoreTax system in early 2025 has created new challenges in corporate tax management, particularly regarding invoice delays and administrative sanctions. This study aims to analyze the causal relationship between invoice delays, administrative sanctions, and accounting strategies while developing optimal strategies for the CoreTax era. The research methodology employed a quantitative approach with a cross-sectional survey design involving 412 companies that have implemented CoreTax. Data were analyzed using Structural Equation Modeling with Partial Least Squares approach to test structural models and causal relationships between variables. Results indicate that invoice delays have a significant positive effect on administrative sanctions (β = 0.585, p < 0.001), administrative sanctions serve as full mediators in relationships with preventive and mitigation strategies, while accounting strategies positively influence compliance performance (β = 0.672, p < 0.001). Responsive strategies demonstrate the highest effectiveness in managing delay consequences, while CoreTax technology integration with accounting systems requires enhanced technological literacy. Findings confirm the importance of developing integrated accounting strategies encompassing early warning systems, predictive analytics, and risk mitigation mechanisms to optimize tax compliance in the digital era. Keywords: CoreTax, Invoice Delays, Administrative Sanctions, Accounting Strategies, Tax Compliance